The three relationships between the accurate traditional speech and the theories of the physics of the universe in the thought of Muhammad Basil Al-Tai - Latif, Riyad Saeed (Al-Adab Journal, 2022)
This research is summarized by completing the study of the five principles that we have identified as five relationships in linking the subtleties of traditional speech with the physical theories of the universe of an Iraqi cosmologist, Prof. Dr. Muhammad Basil Al-Taie. The first is the principle of division and separation, and the second is the principle of occurrence, and here we are completing the remaining three principles, the principle of renewal of creation, the principle of permissibility and space, and the principle of overlapping time and space.